204 Role of minimally invasive surgery versus open approach on the clinical and surgical outcome in patients with early stage uterine carcinosarcomas: a retrospective study. (13th November 2020) - Corrado, G; Ciccarone, F; Cosentino, F; Legge, F; Rosati, A; Arcieri, M; Turco, LC; Certelli, C; VIzza, E; Fanfani, F; Scambia, G; Ferrandina, G
Abstract : Objectives: The aim of this retrospective study was to compare surgical and survival outcome in only patients with early stage uterine carcinosarcomas (UCSs) managed by laparotomic surgery (LPT) versus minimally invasive surgery (MIS). Methods: Data were retrospectively collected in 4 Italian different institutions. Inclusion criteria were: UCS diagnosis confirmed by the definitive histological examination, and stage I or II according to the FIGO staging system. Results: Between August 2000 and March 2019, the data relative to 150 patients bearing UCSs were collected: of these, 82 were defined as early stage disease (stage I-II) based on the histological report at the primary surgery, and thus were included in this study. Forty patients were managed by LPT, and 42 patients were managed by MIS. The operative time was lower in the MIS group versus the LPT group; the median estimated blood loss was less in the MIS group compared to the median of LPT group (p value <0.0001). The number of days was shorter in the MIS patients (p value <0.0001). Only 1 intra-operative complication was documented in the LPT group. There were 6 (15.0%) post-operative complications; they were more frequent in the LPT group nonetheless there was no statistically significant difference (p value=0.10). There was no difference in the disease free survival (DFS) and overall survival (OS) between the two groups. Conclusion: There was no difference in terms of oncologic outcome between the two approaches, in face of a more favourable peri-operative and post-operative profile in the MIS group.